Predictive value of serum irisin for chronic heart failure in patients with type 2 diabetes mellitus - Berezin, A. A.; Fushtey, I. M.; Pavlov, S. V.; Berezin, A. E.; Фуштей, Іван Михайлович; Павлов, Сергій Васильович; Березін, Олександр Євгенійович (My University, 2022)
We hypothesize that serum irisin can have additional discriminative potency for heart failure (HF) in individuals with type 2 diabetes mellitus (T2DM). The study group comprised 226 consecutive T2DM patients (153 patients with any HF phenotypes and 30 patients without HF) aged 41 to 65 years. The plasma levels N-terminal brain natriuretic propeptide (NT-proBNP) and irisin were detected by ELISA at the baseline of the study. We found that the most appropriate cut-off value of irisin (HF versus non-HF) were 10.4 ng/mL (area under curve [AUC] = 0.96, sensitivity = 81.0%, specificity = 88.0%; P = 0.0001). Cutoff point of NT-proBNP that distinguished patients with HF and without it was 750 pmol/L (AUC = 0.78; sensitivity = 72.7%, specificity 76.5%, p = 0.0001). Using multivariate comparative analysis we established that concentrations of irisin < 10.4 ng/mL (odds ration [OR] = 1.30; P = 0.001) and NT-proBNP > 750 pmol/ mL (OR = 1.17; P = 0.042), left atrial volume index (LAVI) > 34 mL/m2 (OR = 1.06; P = 0.042) independently predicted HF. Irisin being added to NT-proBNP improved predictive modality for HF, whereas combination of NT-proBNP and LAVI > 34 mL/m2 did not. In conclusion, we established that irisin had independent predicted potency for HF in patients with established T2DM.
Keywords: Type 2 diabetes mellitust; heart failure; irisin; natriuretic peptides; predictive model